Antiepileptic drugs prevent changes induced by pilocarpine model of epilepsy in brain ecto-nucleotidases - Giana de Paula Cognato (2022)
Submitted by Biblioteca Suporte PUCRS (biblioteca.suporte@pucrs.br) on 2022-09-06T12:48:44Z No. of bitstreams: 2 Antiepileptic_drugs_prevent_changes_induced_by_pilocarpine_model_of_epilepsy_in_brain_ectonucleotidases.pdf: 321971 bytes, checksum: d31bc7c6df99f6d81aac9324617943c6 (MD5) Antiepileptic_drugs_prevent_changes_induced_by_pilocarpine_model_of_epilepsy_in_brain_ectonucleotidases.pdf: 321971 bytes, checksum: d31bc7c6df99f6d81aac9324617943c6 (MD5)